Reverse Period Doublings In A 3ᴿᴰ Order Nonlinear And Autonomous Electric Circuit - Kyprianidis, Ioannis M.; Fotiadou, Maria E. (İstanbul Kültür Üniversitesi Yayınları, 2006)
We have studied the dynamics of Chua's canonical circuit, when the v-i characteristic of the nonlinear resistor of the circuit is a smooth cubic function. Unlike the monotone bifurcation behavior of the members of Chua' s circuit family with a piecewise linear resistor, reverse period doublings, as a parameter of the circuit is varied in a monotone way, have been observed in the circuit we have studied. Dynamics of the circuit is very sensitive to initia\ conditions, as chaotic attractors coexist with period-l limit cycles.
Keywords: nonlinear electric circuit; chaos; antimonotonicity; cubic nonlinearity; bubbles; crisis; coexisting attractors; doğrusal olmayan elektrik devresi; kaos; kübik nonlineerlik; kabarcıklar; kriz; çekicilerin eşlik